Gender and Locale based Variations in Psychological Well-being among Undergraduate Students - Kaur, Suprit; Upreti, Rashmi; Vig, Deepika (International Journal of Bio-resource and Stress Management, 2025)
This study was conducted over a period of twelve months during (April, 2023 to November, 2024) with data exclusively collected from undergraduate students in the Ludhiana district, Punjab, India to assess psychological well-being and to investigate gender-based and locale-based differences in psychological well-being within this population. The sample consisted of 380 students, equally divided between rural (n=190) and urban (n=190) backgrounds from Ludhiana district and further balanced by gender (95 males and 95 females). Participants were selected through the draw-a-lot method from five representative colleges in both rural and urban areas of the Ludhiana district. Data collection was conducted using a Self-Structured Information Sheet and the Psychological Well-Being Scale by Sisodia and Choudhary (2012). Analysis revealed that male students reported higher psychological well-being compared to their female counterparts. Significant gender differences were observed in the domains of efficiency and mental health, with a higher percentage of boys achieving elevated levels of well-being in these areas. These findings were consistent with the mean score analysis, which highlighted significant gender disparities in these specific domains, while other domains showed no notable differences between genders. Overall, the results emphasized that boys generally experience higher psychological well-being than girls. Further analysis of locale-based differences revealed no significant difference between rural and urban girls, and between rural and urban boys. This highlighted the importance of addressing the underlying socio-cultural, environmental, and psychological factors contributing to these disparities.